A prospective observational treatment study of aerococcal urinary tract infection. Issue 4 (April 2018) - Oskooi, Mohammad; Sunnerhagen, Torgny; Senneby, Erik; Rasmussen, Magnus
Highlights: A prospective observational trial on treatment of aerococcal UTI was conducted. Persons with aerococcal bacteriuria were older and a majority had UTI. Nitrofurantoin was the most commonly prescribed antibiotic. Overall clinical success was 84% for Aerococcus urinae UTI and 68% for Aerococcus sanguinicola UTI. Microbiological success was 78% for A. urinae UTI and 58% for A. sanguinicola UTI. Abstract: Objectives: Aerococcus urinae and Aerococcus sanguinicola cause urinary tract infections (UTIs) and antibiotic treatment recommendations are solely based on in vitro findings and limited clinical experience. Our objective was to investigate the effectiveness of different treatment strategies in aerococcal UTI through a prospective observational study. Methods: Urine samples with aerococci were identified and patients were enrolled. The aerococci were subjected to Etests. Information on clinical symptoms, and the treatment given, was collected. Patients were interviewed after the conclusion of treatment to assess clinical cure and a control urine culture assessed the microbiological cure. Results: Of 31, 629 urine samples, 144 grew aerococci and fulfilled the inclusion criteria. 91 patients gave consent and the 72 patients with UTI were assessed for treatment outcome. 53 patients had A. urinae UTI, while 19 had A. sanguinicola UTI. Nitrofurantoin was most commonly prescribed, achieving clinical and microbiological success in 71/76% of cases of A. urinae UTI, and 42/50% of cases of A. sanguinicola UTI. Pivmecillinam achieved success in patients with A. urinae cystitis and ciprofloxacin in patients with pyelonephritis. Conclusions: Our results support that nitrofurantoin is a valid option for the treatment of cystitis caused by A. urinae .